2010
DOI: 10.1111/j.1439-037x.2010.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

FLOODING STRESS: The Effects of Planting Pattern and Water Regime on Root Morphology, Physiology and Grain Yield of Rice

Abstract: IntroductionRice production needs to be increased by 50 % or more above the current production level to meet the rising food demand. Much of the demand will be arising from Asia, which is the home of two-third of the world's population and where 90 % of total rice supply is grown in diverse environments (IRRI, 2008). Current challenges Keywords plant senescence; planting pattern; root oxidizing activity; single seedling; system of rice intensification; water regime Correspondence A. MishraAbstract Field experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 18 publications
(40 reference statements)
5
37
1
Order By: Relevance
“…Plants grown under intermittent irrigation of three-day intervals were significantly taller compared to the others at both panicle initiation and heading stages, whereas comparable results were observed between CF and intermittent irrigation intervals of seven days at heading. This continues to support the findings of [12,42,43] among others, who detailed that rice does not need to be continuously submerged to produce high yields if adequate water is provided at critical growth stages. The SRI practices employed enhanced plant growth and tillering ability to improve plant/culm height and strengthen tillers.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Plants grown under intermittent irrigation of three-day intervals were significantly taller compared to the others at both panicle initiation and heading stages, whereas comparable results were observed between CF and intermittent irrigation intervals of seven days at heading. This continues to support the findings of [12,42,43] among others, who detailed that rice does not need to be continuously submerged to produce high yields if adequate water is provided at critical growth stages. The SRI practices employed enhanced plant growth and tillering ability to improve plant/culm height and strengthen tillers.…”
Section: Discussionsupporting
confidence: 80%
“…Chlorophyll content were lowest under CF regimes, indicating that leaf senescence occurred faster compared to plants grown under intermittent irrigation. Such observations were also documented by [42], who confirmed that higher levels of chlorophyll are maintained in the leaves while fluorescence efficiency and photosynthetic rate can be increased under AWD-SRI compared with CF. Thakur et al [5] highlighted that SRI leaves had higher light utilization capacity and a greater photosynthetic rate which ensures sufficient supply of assimilates to the roots for their development and longevity.…”
Section: Discussionsupporting
confidence: 63%
“…Although chlorophyll content of the flag leaves and third leaves decreased with ripening, the rate of decrease is different among planting densities, and chlorophyll content was higher with wider spacing (30 by 30) compared to narrow spacing (20 by 20) (Mishra and Salokhe 2010). This high chlorophyll content with wider spacing was attributed to higher root-oxidizing activity of more widely-spaced rice plants (Mishra and Salokhe 2010). The SPAD value of the flag leaf of hybrid rice with lower plant density grown under SRI management was higher than with higher plant density at the flowering stage (Lin et al 2009).…”
Section: Plant Spacingmentioning
confidence: 90%
“…Root length density of rice plants grown under SRI (intermittent flooding) was higher than under continuously flooded management, especially in the middle and late ripening growth stages of the rice plants (Mishra and Salokhe 2010). Significantly higher root dry weight per hill and per unit area with SRI compared to recommended management practices (RMP; kept flooded to maintain a ponded water of 5-8 cm depth during the entire vegetative stage of rice plant) was observed during the early ripening stage of the rice plants.…”
Section: Water Managementmentioning
confidence: 92%
See 1 more Smart Citation